Peningkatan Angka Kejahatan Pencurian pada Masa Pandemi dalam Tinjauan Kriminologi dan Hukum Pidana Islam - Mamluchah, Laila; Mubarok, Nafi' (Al-Jinayah : Jurnal Hukum Pidana Islam, 2020)
This article discusses the increase of number in theft crimes during the pandemic based on criminology and Islamic criminal law. The condition of the world today that struck by a pandemic gave many impacts on various aspects of life, one of which is the economy. The “stay at home” policy to reduce the spread of the Covid-19 outbreak resulted in many massive layoffs, which in turn weakens the economy's community, which on the other hand increased the theft crime rate. According to criminology, the increase of theft crime during the pandemic is affected by sociological factors. It is because of those with a weak economic capacity who cannot meet their basic needs. Besides, there is also an imbalance in the structure of society, which then results in dysfunction of social construction. Meanwhile, in the study of Islamic criminal law, the reason for the occurrence of criminal acts is due to the inability of humans to maintain their nature and the presence of outside influences. Of course, this also rejects the theory of the existence of a relationship between poverty and crime, because basically, those who in material poverty and material wealth all have the potential to commit crimes so that all depend on their return to their respective nature.